Implant Bed Preparation with an Erbium, Chromium Doped Yttrium Scandium Gallium Garnet (Er,Cr: YSGG) Laser Using Stereolithographic Surgical Guide - Seymen, Gulin; Turgut, Zeynep; Berk, Gizem; Bodur, AyÅŸen (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Implant bed preparation with laser is taken into consideration owing to the increased interest in use of lasers in hard tissue surgery. The purpose of this study is to determine the deviations in the position and inclination between the planned and prepared implant beds with Erbium, Chromium doped Yttrium Scandium Gallium Garnet (Er,Cr: YSGG) laser using stereolithographic (SLA) surgical guides. METHODS: After 3-dimensional (3D) imaging of six sheep lower jaws, computed tomography (CT) images were transformed into 3D models. Locations of implant beds were determined on these models. Two implant beds in each half jaw were prepared with an Er,Cr:YSGG laser system and a conventional drilling method using a total of 12 SLA surgical guides. A new CT was taken to analyze the deviation values between planned and prepared implant beds. Finally, a software program was used to superimpose the images on 3D models, then the laser and conventional drilling groups were compared. RESULTS: Differences of mean angular deviations between the planned and prepared implant beds were 5.17±4.91° in the laser group and 2.02±1.94° in the conventional drilling group. The mean coronal deviation values were found to be 0.48±0.25 mm and 0.23±0.14 mm in the laser group and conventional drilling group, respectively. While the mean deviation at the apex between the planned and prepared implant beds were 0.70±0.26 mm and 0.26±0.08, the mean vertical deviations were 0.06±0.15 mm and 0.02±0.05 mm for the laser group and the conventional drilling group, respectively. CONCLUSION: It is possible to prepare an implant bed properly with the aid of Er,Cr:YSGG laser by using SLA surgical guide.